Gender and Urbanity Group Comparisons of the Impact of a Health Risk Factor on Juvenile Recidivism - Dembo, Richard (American journal of criminal justice, 2022)
Research has demonstrated justice-involved adolescents are at high risk for substance use, acquiring sexually transmitted infections (STIs), and engaging in risky sexual practices. Substance use and risky sexual practices have public health consequences and may place youths at risk for other long-term outcomes, such as recidivism. This study utilized data collected at two juvenile assessment centers (JACs) for 4033 adolescents criminally arrested/charged to explore gender (male vs. female) and location (urban JAC vs. rural JAC) group differences in health risk and recidivism. Results indicated a single factor of health risk comprised of biological assay test results for marijuana use and STIs and self-reported number of sexual partners fit the data for each of the groups. This health risk factor significantly predicted recidivism (return to JAC) for urban males and rural females, and near significantly predicted recidivism for rural males. Age and race differences were found in associations with the health risk factor and recidivism. The results confirm that marijuana use and sexual behavior reflect a risk propensity and should be considered when assessing needs for intervention services for justice-involved youths.